2010
DOI: 10.1523/jneurosci.2747-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Cells in Piriform Cortex Receive Convergent Input from Distinct Olfactory Bulb Glomeruli

Abstract: Pyramidal cells in piriform cortex integrate sensory information from multiple olfactory bulb mitral and tufted (M/T) cells. However, whether M/T cells belonging to different olfactory bulb glomeruli converge onto individual cortical cells is unclear. Here we use calcium imaging in an olfactory bulb-cortex slice preparation to provide direct evidence that neurons in piriform cortex receive convergent synaptic input from different glomeruli. We show that the combined activity of distinct glomerular pathways rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 23 publications
3
72
0
1
Order By: Relevance
“…In slices, focal activation of a single glomerulus was found to activate disperse layer II-III Pir neurons. Similar to Pir odor responses, stimulation of different glomeruli activated sparse but distinct ensembles in overlapping cortical areas with ∼10% of neurons responding to two glomeruli (Apicella et al, 2010). Simultaneously, stimulation of two glomeruli activated twice as many cells than the sum activated by either pathway alone.…”
Section: Odor Processing In Olfactory Cortexmentioning
confidence: 84%
“…In slices, focal activation of a single glomerulus was found to activate disperse layer II-III Pir neurons. Similar to Pir odor responses, stimulation of different glomeruli activated sparse but distinct ensembles in overlapping cortical areas with ∼10% of neurons responding to two glomeruli (Apicella et al, 2010). Simultaneously, stimulation of two glomeruli activated twice as many cells than the sum activated by either pathway alone.…”
Section: Odor Processing In Olfactory Cortexmentioning
confidence: 84%
“…First, 20-40% of piriform pyramidal cells that respond to an odor mixture fail to respond to the individual components of the same mixture [34 ]. Second, simultaneous stimulation of multiple glomerular sites is sufficient to increase activity in many pyramidal neurons distributed throughout piriform cortex, though these cells are not activated by stimulation of individual glomeruli [38,39]. Together, these results argue for a cooperative recruitment of pyramidal neurons when odor mixtures are presented.…”
Section: Piriform Cortex-connectivity and Codingmentioning
confidence: 96%
“…This means that overall topography in the OB is not preserved in many areas of the olfactory cortex including piriform cortex. Transsynaptic retrograde tracing and functional mapping demonstrated that piriform neurons receive convergent inputs from multiple glomeruli [26,66,80,81]. In addition, 2-photon calcium imaging of piriform cortex failed to find any topographic representation of odors [82].…”
Section: Cortical Projection Of Mitral/tufted Cellsmentioning
confidence: 99%